The changing face of warfare in the 21st century - Simons, Greg; Chifu, Iulian (Routledge, 2018)
This study discusses salient trends demonstrated by contemporary warfare of these first years of our 21st Century. The authors reinforce previous notions of Fourth Generation Warfare but most importantly detail the specific workings of new components and illustrate how they have displaced or modified the theory and practice of warfare beyond the basic divisions of conventional and unconventional warfare as witnessed in the preceding century.